Cherenkov Radiation–Based Coincidence Time Resolution Measurements in BGO Scintillators - Gonzalez-Montoro, Andrea; Pourashraf, Shirin; Cates, Joshua W.; Levin, Craig S. (Frontiers in Physics, 2022)
Bismuth Germanate Oxide (BGO) scintillators can be re-introduced in time-of-flight positron emission tomography (TOF-PET) by exploiting the Cherenkov luminescence emitted as a result from 511 keV interactions. Accessing the timing information from the relatively few emitted Cherenkov photons is now possible due to the recent improvements in enhanced near ultra-violet high-density (NUV-HD) silicon photomultiplier (SiPM) technology, fast and low noise readout electronics, and the development of efficient data post-processing methods. In this work, we aim to develop a scalable detector element able to achieve excellent coincidence time resolution (CTR) required for TOF-PET using BGO scintillator elements of various lengths. The proposed detector element is optically coupled to 3.14 × 3.14 mm2 NUV-sensitive SiPMs mounted on a custom design circuit board. In particular, we have evaluated the CTR performance of BGO crystal elements of dimensions 3×3×3 mm3, 3×3×5 mm3, 3×3×10 mm3, and 3×3×15 mm3, with chemically etched surfaces and wrapped in Teflon tape. To achieve excellent CTR performance we apply state-of-the-art post-processing methods during data analysis. Best values of 156 ± 6 ps, 188 ± 5 ps, 228 ± 8 ps and 297 ± 8 ps CTR FWHM have been achieved for the 3, 5, 10 and 15 mm length BGO crystals, respectively. These values improve to 105 ± 6 ps, 127 ± 8 ps, 133 ± 4 ps and 189 ± 8 ps CTR FWHM, when only considering the Cherenkov component of the timing signal, which is extracted by considering the events with the fastest rise time (20% of the total data). The accurate classification of the events based on their rise time is possible thanks to the implementation of a dual threshold approach that sets the lower threshold below one light photon equivalent level, and the upper one above the signal amplitude of a single photosensor.